STRATEGI GURU SEJARAH KEBUDAYAAN ISLAM DALAM MEREKONSTRUKSI MATERI TENTANG PEPERANGAN DALAM PERADABAN ISLAM DI MA ALI MAKSUM KRAPYAK YOGYAKARTA - Khasan Bisri (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2016)
In the writing of Islamic cultural history, there are almost all the books write about war. The lessonbooks of Islamic cultural history in the school also not inseparable from material about war. Thismatter if not addressed properly by the teachers and students there was great potential false perceptioneven erroneous, so there needs the right strategy for the students so that has not wrong perceptionabout war in Islam. This research has purposes for knowing Islamic cultural history teacher strategyin reconstruction the material about war and its impact to the students. Data collection was done byinterview, observation, documentation, and checking data validation with triangulation. The teachermethod to reconstruct war material in Islamic civilization by explaining to the students the jihad anddakwah concept firstly, then the background of war happening, value / ibrah / moral value that canbe taken from the war occurrence, and also explains various phenomenon or actual issues that washappening recently, and then connected with that war material. The impact for the students is whenthe teacher conveys the war material attractively and fun can be divided into two, cognitive impact andattitude impact.Keywords : Islamic Cultural History Strategy, Material Construction, War.